PEMBELAJARAN GUIDED INQUIRY DENGAN PENDEKATAN CTL PADA MATERI EKOLOGI DAN KEANEKARAGAMAN HAYATI TERHADAP PEMAHAMAN KONSEP - Fahim Noor Rahma; Erman Erman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The science conceptual understanding of Indonesian students is still relatively low, partly due to learning practices that are less actively engaging and contextual. This study aims to analyze the effect of the Guided inquiry learning model with the Contextual Teaching and Learning (CTL) approach on students' conceptual understanding of Ecology and Biodiversity. This research is a quantitative study with a quasi-experimental design using a nonequivalent control group design. The sample consisted of two classes: VII-F as the experimental class (Guided inquiry learning with CTL) and VII-G as the control class (Guided inquiry only) at SMP Negeri 61 Surabaya. Data were collected through conceptual understanding tests (pretest-posttest), learning implementation observation sheets, and student response questionnaires. The results showed a significant difference in the improvement of conceptual understanding between the experimental class (N-gain 0.59) and the control class (N-gain 0.47), with a Sig. (2-tailed) value of 0.024 < 0.05. The effect size calculation yielded a Cohen's d value of 0.628, which falls into the large category, indicating high effectiveness. The implementation of learning in both classes was very well executed, and student responses to the learning in the experimental class were very positive (86.41%). It is concluded that the Guided inquiry learning model with the CTL approach is effective and significant in improving students' conceptual understanding compared to Guided inquiry learning alone.